STRATEGI KOMUNIKASI PEMASARAN AGROWISATA TAMAN KUPU-KUPU SINARWANGI PARK LAND BOGOR DALAM MEMBENTUK BRAND AWARENESS - Dimas Agung Laksono Raharjo; Layung Paramesti Martha; Prasetyo Adinugroho (UNIVERSITAS PAKUAN, 2019)
ABSTRACTThis study aims to find out how the marketing communication strategy carried out by Taman Kupu-Kupu Sinarwangi Park Land Bogor in Forming Brand Awareness and to find out what factors are supporting and inhibiting the implementation of marketing communication strategies in Taman Kupu-Kupu Sinarwangi Park Land Bogor. This study uses a qualitative research approach that produces descriptive data in the form of written words and the data methods used are primary data and secondary data. Data collection techniques in this study were interviews, observation, and documentation.The results of this study emphasize the marketing communication strategy that has been carried out by Taman Kupu-Kupu Sinarwangi Park Land Bogor in forming brand awareness. Taman Kupu-Kupu Sinarwangi Park Land Bogor carries out a marketing communication strategy so that the Taman Kupu-Kupu Sinarwangi Park Land Bogor brand is recognized by the surrounding community, especially Bogor. The strategies used include identifying targets, determining communication objectives, designing messages, selecting personal and non-personal media communication channels, compiling a total communication budget, determining the promotion mix, implementing integrated marketing communication programs (IMC), and gathering feedback. There are supporting factors in the implementation of marketing communication strategies carried out by Taman Kupu-Kupu Sinarwangi Park Land Bogor, namely by presenting their superiority on social media Facebook and Instagram and utilizing school visits by interacting directly with teachers through information media through word of mouth. While the inhibiting factor is the limited costs and human resources. Keywords: Marketing Communication Strategy, Taman Kupu-Kupuwangi Park Land Bogor, Forming Brand Awareness